Sosialisasi Dampak Smartphone Terhadap Peningkatan Ekonomi di SMK Armaniyah Cikarang - Sukron Mamun; Sakum; Sarwo Edy; Nenda; Saiful Mukti Ali (Jurnal Pengabdian Pelitabangsa, 2021)
Smartphones have become very popular and profound technological devices accessible to many people around the world. Technological developments and the presence of smartphones have had a major impact on various aspects of human life, including in the economic context of society. This study aims to present a summary of the impact of smartphones on improving the community's economy. In this abstract, we will explain some of the main impacts of smartphone use on improving the community's economy. First, smartphones have facilitated access to information and communication, which enables people to participate in the digital economy more efficiently. The use of online applications and platforms has increased connectivity and the ability to conduct business, transactions, and collaborate with other parties. However, it is important to recognize that the positive impact of smartphones on improving the people's economy must also be managed wisely. Excessive or unwise use can lead to negative impacts, such as over-reliance on technology and data privacy issues. In conclusion, smartphones have a significant role in improving the people's economy. With easier access to information and communication, wider economic choices, and support for entrepreneurship and education, people can use smartphones to optimize their economic potential. It is important for governments, institutions and other stakeholders to support the wise and sustainable use of smartphones in order to achieve sustainable and inclusive economic growth.